PERBEDAAN PERILAKU KERJA INOVATIF BERDASARKAN KARAKTERISTIK INDIVIDU KARYAWAN - Etikariena, Arum (Faculty of Psychology, Diponegoro University, 2018)
In recent years, research on innovation in organizations, particularly innovative work behaviors, has developed considerably. The objective of the study were to examine the role of individual characteristics such as age, gender, educational background, ethnic’s background, tenure and length in current position which presumably would have an impact on the formation of innovative work behaviors. The study is quantitative study with non-experimental design, conducted on 279 respondents working in a Syariah Bank and a television company. The measuring tool used is the Innovative Work Behavior Scale. Demographic data were asked to be completed in the questionnaire. Data were analyzed using t-test, one-way Anova, and crosstabs analysis. The results show that innovative work behavior differs significantly based on age (χ2(3, 276) = 17.54; p < .001), educational background (χ2 (4, 275) = 8.18; p = .04), and tenure (χ2(2, 277) = 6.98; p = 0.03), but has no significant difference based on gender (χ2(2, 277) = 1.68; p = .20), ethnic background (χ2(13, 266) = 8.12; p = .78) and length in the current position (χ2(3, 276) = 3.81; p = .15). Thus, the results of this study will contribute to enrich the knowledge about innovative work behavior in Indonesia. Furthermore, this result will also be a consideration for dealing with employees to encourage innovative work behavior.